The Best Machine Learning Model for Fraud Detection In Banking Sector: A Systematic Literature Review - Yanto Yanto; Lisah Lisah; Re’gina Tandra (Komunitas Dosen Indonesia, 2024)
In today's financial landscape, banks face an increasing number of sophisticated fraud attempts, driven by advancements in technology and the growing volume of digital transactions, especially accelerated by the COVID-19 pandemic. This systematic literature review (SLR) aims to identify the most effective machine learning models for fraud detection in the banking sector, based on open access articles published between 2014 and 2024. Data was collected using Dimensions.ai, focusing on keywords such as